Enhancing thermodynamic efficiency of energy intensive distillation columns via internal heat integration - Olujić, Žarko (Array, 2008)
Summary: As demonstrated in the present simulation study, taking propylene/propane splitter as base case, an internally heat integrated distillation column (HIDiC), with rectification section operating at higher pressure and temperature than the stripping section, offers significant potential for energy saving compared to energy requirements associated with operation of conventional and heat-pump assisted distillation columns. The rectification section of a propylene/propane splitter contains usually two times more stages than the stripping section, implying a number of heat coupling possibilities, which appears to be strongly influencing the thermal efficiency of the HIDiC. The configuration with the stripping section stages thermally interconnected with the same number of stages in the upper part of the rectification section emerged as the most efficient configuration, allowing a reduction in energy use in the range 30 to 40 % compared with a state of the art heat-pump assisted column, depending on the trade off between the operating compression ratio and the heat transfer area requirement, the latter one being the key limiting factor